NUCLEOTIDES IN NUTRITION OF CHILDREN - T.G. Reshetova; N.G. Sokolova ("Paediatrician" Publishers LLC, 2010)
Nucleotides are used in different significant biological processes, they have prebiotic, bifidogenic, immunomodulating, trophic effect on tunica mucosa of gastrointestinal tract, they also influence lipid and carbohydrate metabolism. The literature review describes influence of nucleotides and changes of its volume in cow's and breast milk on growth and development of children. Key words: children, nucleotides, nutrition, immune system, breast milk. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(6):31-36)